Packaging Design Model Of Talang Salted Fish Processing Industry Using Value Engineering Method - Amri, A; Muhammad Jalil, Saifuddin; Bahri, Syamsul; Fatimah, Fatimah (International Journal of Engineering, Science and Information Technology, 2022)
One of the products that need attention, especially related to packaging, is the Talang Salted Fish product, which has been selling Talang Salted Fish without using packaging. So that this study aims to design the packaging of talang salted fish to add selling value which can later be an attraction for consumers to buy it. The method used is value engineering and the analytical hierarchy process (AHP). The value engineering method is applied to increase the value, performance, and cost of packaging design consisting of brand criteria, net weight measurement, product identity, attractiveness, color suitability, typography, and font size. The Analytical Hierarchy Process Â method is applied at the analysis stage to help determine the priority criteria in accordance with the wishes of consumers. The results showed that the alternative design with the highest performance value was alternative 1 (A-B-D-E), namely the design with packaging materials made of transparent plastic, the colors used were bright, the packaging was rectangular and all capital letters were used. This selected alternative design has a value of 0.039. This value is obtained from the performance of 38.9 and the cost of Rp. 1000 per pack.